Ethical considerations of deep brain stimulation for treatment refractory schizophrenia: surveying stakeholders - Judith M. Gault; Nicola Cascella; Nidal Moukaddam; Stephanie Lehto; Patrick Hosokawa; Paul S. Appelbaum; Akira Sawa; Jocelyn Lippman-Bell; William S. Anderson; Wayne Goodman; Sameer A. Sheth; Daniel Kramer; et al. (BMC Psychiatry)
Abstract Introduction Ethical concerns have been raised by both current and historically controversial neurosurgical interventions for treatment-refractory schizophrenia and schizoaffective disorder (TR-SZ). Considering advances in next-generation deep brain stimulation (DBS), initial success in treating a few cases of TR-SZ, and how challenging trial enrollment is, transparency and disseminating knowledge about DBS is important, as is input from involved groups. Here information was presented about DBS as an experimental treatment option for TR-SZ to stakeholders to gauge enthusiasm after consideration of potential risks and benefits. Methods Stakeholders were presented with information about DBS (total n = 629). Opinions about whether DBS should be an option for people with TR-SZ and acceptable response rates considering DBS risks were collected from research participants with SZ, treatment-refractory Parkinson’s disease (TR-PD) approved for DBS, caregivers for either SZ or TR-PD participants, and attendees at medical school presentations. In addition, the attendees were asked to decide whether DBS is appropriate for 4 cases who want DBS, one with PD, 2 with OCD and 1 with SZ. Chi-square, pairwise comparisons, and Duncan Multiple Range Test were performed with significance at p < 0.05. Results Most (83%) research participants and presentation audience members agreed that DBS should be an option for TR-SZ and 40% thought the potential benefits outweigh the risks of DBS with at least a 41–60% response rate. Audience approval of DBS was similar for the PD (30%), SZ (52%) and the OCD case with psychosis (56%), but there was a higher rate of approval (77%) for the OCD case whose compulsions involved self-harm. The majority (73–86%) of the audience thought that they would want to try DBS if they had TR-PD, TR-OCD, or TR-SZ. Conclusions Despite difficulty in recruiting patients for DBS clinical trials for TR-SZ, the consensus among 83% of stakeholders was that DBS should be an option for people with severe TR-SZ. Our approach to disseminate general knowledge then gather opinions among diverse stakeholders was to ensure the development of DBS clinical trials for the new indication TR-SZ is a relevant option despite the known difficulties in enrollment. These findings may help prevent disparities in access to advanced DBS therapeutics.